MYOD1 c.365G>T, p.L122R Variant Detection by Droplet Digital PCR (ddPCR). (28th October 2021) - Lip, V; Grimmett, L; Diaz, C; Cantave, J; Yang, W; Harris, H; Tsai, H K; Church, A J; Harris, M H
Abstract: Introduction/Objective: Rhabomyosarcomas (RMS) are a group of skeletal muscle tumors that include embryonal, alveolar, pleomorphic, spindle cell/sclerosing subtypes (SC/SRMS). Spindle cell RMS occurs in both adult and pediatric populations, and is associated with either more aggressive or better clinical outcomes respectively. A recurrent hotspot variant in MYOD1, p.L122R (NM_002478.4 c.365G>T), has been described in SC/SRMS. The classification of this diagnosis is evolving, with VGLL2 and NCOA2 fusions defining the diagnosis in young children, and MYOD1 p.L122R defining the diagnosis in older children. The MYOD1 p.L122R variant seems to be associated with more aggressive disease, and may be increasingly used in risk stratification with intensification of treatment. Methods/Case Report: A digital droplet PCR (ddPCR) assay was used to detect the MYOD1 p.L122R in DNA samples with RMS. Patients and controls were coded as positive or negative, and tested for association with clinical features and outcome. Results (if a Case Study enter NA): Known-positive cohort of samples was limited by the extreme rarity of this tumor. "Known-positive" status was established by confirmation of the variant with an external clinically-validated assay. The six known positive samples were assessed by ddPCR for the presence of MYOD1 L122R. The L122R variant was detected in all six variants for a sensitivity of 100%. DNA and/or TNA obtained from known wild-type FFPE and frozen material was assessed, for a total of nine unique samples (1 synthetic, 8 patient-derived). All 9 samples were wild- type, with no positive droplets detected, for a specificity of 100%. Conclusion: Our MYOD1 c.365G>T, p.L122R variant detection by droplet digital PCR (ddPCR) assay is a robust, reproducible, specific and sensitive method to detect the MYOD1 hotspot mutation.